Perilla frutescens: a potential ingredient for the enhancement of white bread as a source of Omega-3 - Silva, Marcos Vieira da; Silva, Andréia Vieira da; Bonafé, Elton Guntendorfer; Souza, Nilson Evelázio de; Visentainer, Jesuí Vergílio (Acta Scientiarum. Technology, 2016)
Perilla frutescens seeds are rich in Omega-3 fatty acids which are important for human health. Intake of fatty acids depends on their presence in popular foods such as white bread. Current study evaluates the replacement of wheat flour by whole perilla at 1, 3 and 5% in white bread processing and its impacts on chemical and sensorial attributes, underscoring Omega-3 amounts. The use of whole perilla increases the Omega-3 content in white bread, balances the ratio n-6/n-3, decreases the specific volume, and maintains the concentration of phenolic compounds and antioxidant activity. The formulation with 1% whole perilla has a better acceptability and supplies 5.63 and 8.19% of the American recommended daily intake of alpha-linolenic acid for adult males and females, respectively. Â